Foreign direct investment, trade, and economic growth: An empirical analysis of Bangladesh - Mohammed Ershad Hussain; Mahfuzul Haque (Economies, 2016)
The study reveals that there is a relationship between foreign direct investments, trade, and growth rate of per capita GDP for Bangladesh with the help of annual time series data for 1973 to 2014. The Vector Error Correction Model (VECM) analysis shows that there is a long-term relationship between these variables. To check the validity of the VECM model, we did a few post-estimation diagnostic tests, and found that the residuals of the regressions have a normal distribution and do not show any auto-correlation. The trade and foreign investment variables have a significant impact on the growth rate of GDP per capita. Because FDI and trade are two important components of economic growth in Bangladesh, it is important to frame policies that promote growth and reduce the barriers for capital flows.
Keywords: F10; F21; F43; O11; O40; O53; 330; foreign direct investments; economic growth; Bangladesh; trade